Jurnal Kemanusiaan (Universiti Teknologi Malaysia, 2010)
Jurnal Kemanusiaan is a multidisciplinary journal consisting of original research articles, book reviews and conference reports on various disciplines covering civilization studies, education, ethics, fine arts, science and technology, organizational skills, language, communication, business management, human resource development, accounting and law.